Development and performance evaluation of a prototype electric hybrid powertrain system for automotive applications - Azhar, Abdul Aziz; Lim, Chon Wei (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/